Broadening the optical bandwidth of quantum cascade lasers using RF noise current perturbations - Pinto, T; Kirkbride, J; Ritchie, G (Optical Society of America, 2018)
We report on the broadening of the optical bandwidth of a distributed feedback quantum cascade laser (QCL) caused by the application of radio frequency (RF) noise to the injection current. The broadening is quantified both via Lamb-dip spectroscopy and the frequency noise power spectral density (PSD). The linewidth of the unperturbed QCL (emitting at ∼5.3  μm) determined by Lamb-dip spectroscopy is 680±170  kHz, and is in reasonable agreement with the linewidth of 460±40  kHz estimated by integrating the PSD measured under the same laser operating conditions. Measurements with both techniques reveal that by mixing the driving current with broadband RF noise the laser lineshape was reproducibly broadened up to ca 6 MHz with an increasing Gaussian contribution. The effects of linewidth broadening are then demonstrated in the two-color coherent transient spectra of nitric oxide.